Analysis of the Effect of Regional Original Revenue Contributions and Balanced Funds on the Level of Regional Financial Independence of Provinces in Indonesia in 2019-2023 - Fania Anjani Suharjo; Saring Suhendro (International Journal of Economics, Management and Accounting, 2025)
This study shows that the contribution of Regional Original Income (PAD) has a significant positive effect on the level of financial independence of provincial regions in Indonesia in 2019-2023. This means that the greater the contribution of PAD, the higher the level of regional financial independence. On the other hand, the General Allocation Fund (DAU) and the Special Allocation Fund (DAK) have a significant negative effect on regional financial independence, indicating that dependence on transfer funds from the central government can hinder regional efforts to increase their fiscal independence. Meanwhile, the Revenue Sharing Fund (DBH) does not show a significant effect on the level of regional financial independence, indicating that although this fund is important, it does not directly contribute to increasing regional financial independence.